DAMPAK KONSUMSI MINUMAN KEMASAN TINGGI GULA TERHADAP KESEHATAN FISIK DAN KONSENTRASI BELAJAR SISWA SEKOLAH DASAR - Gracia Sinuraya (SUAN PUBLISHER, 2025)
This study examines the impact of sugar-sweetened beverage (SSB) consumption on Body Mass Index (BMI) and learning concentration among elementary school students. Using a quantitative cross-sectional design, the research involved 98 students in grades IV–VI selected through stratified random sampling. Data were collected using a validated Food Frequency Questionnaire (FFQ), anthropometric measurements based on BMI-for-age standards, and cognitive assessments through the Digit Span Test and Grid Test. Statistical analysis included descriptive tests, normality tests, correlation analysis, and simple linear regression. The findings indicate a significant positive correlation between frequent SSB consumption and increased BMI (p < 0.05). Additionally, a significant negative correlation was found between sugar intake and post-break concentration levels, suggesting that high glycemic load contributes to decreased sustained attention due to reactive hypoglycemia. The study highlights that obesogenic school environments and low nutritional literacy intensify health and cognitive risks among children. These findings emphasize the urgent need for school-based nutrition regulation and integrated health education programs to prevent obesity and support optimal academic performance in primary education settings